(untitled) (Al-Academy, 2025)
research explores the relationship between digital graphic design and environmental sustainability. With the increasing number of current environmental issues, designers are striving to find ways to incorporate sustainable practices into their designs. This study examines how graphic design contributes to promoting sustainability, the resulting impacts, and the challenges faced by designers, including those related to the adoption of sustainable graphic design. From this research, one can derive innovative and sustainable design practices, understand how to integrate them into work processes, and identify methods to reduce the negative environmental impacts of design activities. The study addresses the concept of environmental sustainability and outlines methodologies for the development of sustainability in the field by applying life cycle thinking systems. It also includes an examination of sustainability principles and how graphic design can be transformed to serve this concept in order to achieve successful sustainable design, with a focus on the social, environmental, and economic responsibility of the graphic designer in today’s world